Relationship of base excision repair pathway-related proteins with immune cell infiltration and prognosis in small cell lung cancer - LI Chaofan; CHEN Tianyi; CHEN Qian (陆军军医大学学报)
Objective‍　‍To observe the expression levels of base excision repair (BER) pathway-related proteins in small cell lung cancer (SCLC) tissues, and analyze their relationship with the prognosis and tumor immune microenvironment. Methods‍　‍A retrospective cohort study was conducted on 74 patients with limited-stage SCLC undergoing surgical treatment in our medical center from December 2018 to June 2023. Immunohistochemical staining was performed to analyze the protein expression of BER pathway components, apurinic/apyrimidinic endonuclease 1 (APE1), 8-oxoguanine DNA glycosylase 1 (OGG1), DNA polymerase β (POLβ), X-ray repair cross-complementing protein 1 (XRCC1), ATP-dependent DNA ligase I (LIGⅠ), and immune cell infiltration markers of CD3⁺ T cells, CD8⁺ T cells, CD68⁺ macrophages in SCLC tissues. Chi-square test was applied to analyze the relationship of BER protein expression and clinicopathological features; Kaplan-Meier survival curve was plotted to evaluate the impacts of BER protein expression and immune cells on disease-free survival (DFS) and overall survival (OS), multivariate Cox regression analysis was utilized to identify DFS prognostic factors, and Spearman correlation analysis was performed to analyze the correlation of BER-immune cell infiltration. In in vitro experiments, transient transfection was applied in H196 cells to overexpress APE1/POLβ/LIGⅠ, respectively. Thus, the cells were divided into negative control (NC, empty vector) and overexpression (OE, target plasmids) groups. CCK-8 and TUNEL assays were employed to determine the effects of OEAPE1, OEPOLβ and OELIGⅠon cell sensitivity to cisplatin. In in vivo experiments, nude mice bearing xenograft tumors were grouped into WT, E3330 (APE1 inhibitor), cisplatin, and cisplatin+E3330 groups to determine the effects of the combination therapy on tumor growth. Results‍　‍There were no significant correlations of the expression levels of key BER pathway proteins with clinicopathological characteristics, including gender, age, smoking history, tumor location, Ki67 index, or TNM stage (all P>0.05). The patients with low expression of APE1, POLβ, and LIGⅠ had obviously higher DFS rates than those with high expression (P<0.05), and the patients with larger proportion of CD3+ T cells also had higher DFS rates than those with smaller proportion (P=0.043). Multivariate Cox regression analysis indicated that tumor TNM stage (HR=2.465) and APE1 expression (HR=2.730) were independent risk factors for the prognosis of SCLC patients (P<0.05). Spearman correlation analysis demonstrated a positive correlation between APE1 and CD8+ T cell proportion in the SCLC patients (r=0.27, P<0.05). In vitro experiments showed that the overexpression (OE) cells (OEAPE1 and OELIGⅠ) exhibited reduced sensitivity to cisplatin than the NC group (P<0.05). Animal experiments indicated that cisplatin+E3330 significant inhibited xenograft tumor growth, indicating enhanced therapeutic efficacy（P<0.01）. Conclusion‍　‍High expression of APE1, POLβ, and LIGⅠ in the BER pathway indicates poor prognosis and low DFS rate in SCLC patients. High expression of APE1 is positively correlated with CD8+T cells, and can be used as an auxiliary marker for SCLC immunotherapy. ［‍